2008
DOI: 10.1007/s10734-008-9172-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and inclusivity at university: a survey of the experiences of lesbian, gay, bisexual and trans (LGBT) students in the UK

Abstract: 1Diversity and inclusivity at university: A survey of the experiences of lesbian, gay, bisexual and trans (LGBT) students in the UK. AbstractThe extent to which UK universities are 'gay friendly' has received some attention in the press. Whilst there are a number of published studies exploring campus climate for Lesbian, Gay, Bisexual and Trans (LGBT) students and/or staff, these are primarily localised studies undertaken in State Universities and Baccalaureate Colleges in the US. The present study is a nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 17 publications
7
112
0
4
Order By: Relevance
“…Globally, attitudes towards LGBT individuals and same-sex relationships have become increasingly more accepting, although active opposition against equal rights for these individuals still exist (Camilleri and Ryan 2006;Ellis 2009;Avery, Chase, Johansson, Litvak, Montero and Wydra 2007). Research, however, indicates that acceptance of same-sex relationships varies across social contexts, e.g., countries and faculties.…”
Section: Couples' Experiences On University Campusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, attitudes towards LGBT individuals and same-sex relationships have become increasingly more accepting, although active opposition against equal rights for these individuals still exist (Camilleri and Ryan 2006;Ellis 2009;Avery, Chase, Johansson, Litvak, Montero and Wydra 2007). Research, however, indicates that acceptance of same-sex relationships varies across social contexts, e.g., countries and faculties.…”
Section: Couples' Experiences On University Campusesmentioning
confidence: 99%
“…These forms of discrimination mostly occurred in public spaces, and were perpetrated by other students (Ellis 2009, 730). Even though the evidence suggests that actual discrimination against LGBT individuals was widespread, most of the participants thought that anti-LGBT attitudes were prevalent to a little/very little extent (Ellis 2009). …”
Section: Couples' Experiences On University Campusesmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are echoed repeatedly throughout the literature, with studies telling the same story of LGBT students facing higher levels of harassment, fear for personal safety, and reporting the concealment of their sexual and gender identities to avoid intimidation (Brown et al, 2004;Ellis, 2009;Gortmaker & Brown, 2006;McKinney, 2005;Rankin, 2005;Waldo, 1998). While all of these studies share the limitations of small sample sizes, and some do not cover transgender students, the students' experiences reported by all of them are remarkably similar.…”
Section: Harassment and Safety On Campusmentioning
confidence: 89%
“…This is echoed by the findings Ellis (2009), andBrown et al (2004), who also found that perceptions of campus climate varied between faculty, staff, graduates and undergraduates, and also that lesbians found the campus climate more hostile than gay men. Gortmaker & Brown (2006) found significant differences in lesbian and gay students' perception of campus climate based on how "out" the individuals were, with out students reporting a more negative campus climate than those who were closeted.…”
Section: General Campus Climatementioning
confidence: 96%